PENGARUH KOMPETENSI GURU, MOTIVASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SMK PARIWISATA TRIATMA JAYA TABANAN - Ni Made Wahyuningsih; Dewiwati Sujadi (Journal Research of Management, 2023)
The purpose of this study was to determine whether there was an effect of teacher competence (X1), motivation (X2) and work environment (X3) on teacher performance (Y) at Triatma Jaya Tabanan Tourism Vocational School. This research includes explanatory research, which is a type of research that aims to determine the relationship between three variables, namely the dependent variable (teacher performance) and the independent variable (teacher competence, motivation and work environment). The population in this study were teachers of the Triatma Jaya Tabanan Tourism Vocational School, which amounted to fifty-six people. The sampling technique uses a saturated sampling method where the entire population is used as a sample. The analysis technique in this research is using descriptive analysis, data quality test, reliability test, classical assumption test, multiple linear regression analysis, t-test analysis, analysis of determination with the help of SPSS 24 software for windows. The results of the analysis show that the regression model is Y = 4.927 + 0.307X1 + 0.615X2 + 0.233X3. The conclusion obtained is that partially teacher competence (X1) has a positive and significant effect on teacher performance (Y) which is indicated by the coefficient b1X1: tcount = 2,382 > ttable (0.05: 52) = 1.674 and Sig t = 0.021 (p<0 ,05). Motivation (X2) has a positive and significant effect on teacher performance (Y) which is indicated by the coefficient b2X2: tcount = 4.162 > ttable (0.05: 52) = 1.674 and Sig t = 0.000 (p <0.05). The work environment (X3) has a positive and significant effect on teacher performance (Y) has a positive and significant effect as indicated by the coefficient b1X1: tcount = 2.673 > ttable (0.05: 52) = 1.674 and Sig t = 0.010 (p<0.05). Teacher competence, motivation and work environment affect the teacher's performance at Triatma Jaya Tabanan Tourism Vocational School by 42.0% while the remaining 58.0% is explained by other variables not examined in this study such as work discipline, technology and others